2015
DOI: 10.1097/adm.0000000000000090
|View full text |Cite
|
Sign up to set email alerts
|

Low Dispositional Mindfulness Predicts Self-medication of Negative Emotion With Prescription Opioids

Abstract: Objectives Although evidence is mounting that opioids are abused to self-medicate negative emotions, little is known about the traits and factors linked to opioid self-medication. One potentially crucial psychological correlate is dispositional mindfulness. Thus, the purpose of this study was to describe the prevalence of opioid self-medication among a treatment-seeking sample of prescription opioid dependent individuals, and to specifically examine the relationship between dispositional mindfulness and opioid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 45 publications
(52 reference statements)
3
21
0
Order By: Relevance
“…From this perspective, emotional distress from comorbid chronic pain and affective dysregulation might impel self-medication motives and thereby increase vulnerability to prescription opioid misuse. Indeed, epidemiological studies indicate that mood and anxiety disorders are often antecedent to the onset of opioid misuse and dependence (Green et al 2011; Martins et al 2012), and in a sample of prescription opioid dependent individuals in acute detoxification and long-term outpatient treatment, 94% reported frequent misuse of opioids to self-medicate negative affect (Garland et al 2014c). Given the common occurrence of prescription opioid misuse as a means of self-medicating negative emotions, it is possible that some participants in the study who were classified as opioid misusers may have suffered from preexisting emotion dysregulation (perhaps due to untreated pain) prior to the onset of opioid use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From this perspective, emotional distress from comorbid chronic pain and affective dysregulation might impel self-medication motives and thereby increase vulnerability to prescription opioid misuse. Indeed, epidemiological studies indicate that mood and anxiety disorders are often antecedent to the onset of opioid misuse and dependence (Green et al 2011; Martins et al 2012), and in a sample of prescription opioid dependent individuals in acute detoxification and long-term outpatient treatment, 94% reported frequent misuse of opioids to self-medicate negative affect (Garland et al 2014c). Given the common occurrence of prescription opioid misuse as a means of self-medicating negative emotions, it is possible that some participants in the study who were classified as opioid misusers may have suffered from preexisting emotion dysregulation (perhaps due to untreated pain) prior to the onset of opioid use.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 21% to 29% of chronic pain patients receiving long-term opioid analgesic pharmacotherapy exhibit opioid misuse behaviors including unauthorized dose escalation or attempts to self-medicate negative affect with opioids (Vowles et al 2015). A recent investigation of treatment-seeking opioid dependent individuals found that 95% reported using opioids to alleviate negative affective states (Garland et al 2015b). Thus, misuse of opioids to regulate emotional well-being may be prevalent in some populations.…”
Section: Introductionmentioning
confidence: 99%
“…6,7,20,22 Recent data showing that low dispositional mindfulness correlates with self-medication of negative emotion with opioids further suggest that mindfulness training may attenuate self-medication. 23 Unfortunately, standard MBSRbased mindfulness training requires extensive time commitment and cost and is not available in most rural primary care settings.…”
Section: Introductionmentioning
confidence: 99%
“…In that regard, chronic pain patients with extensive histories of ACEs may suffer from emotion dysregulation, and turn to opioids as a means of coping with poorly managed affective distress. Such opioid self-medication of negative affect may be quite common among individuals with OUD; for example, in a sample of inpatients with OUD, 95% reported they had used opioids to relieve negative affective states (Garland, Hanley, Thomas, Knoll, & Ferraro, 2015).…”
mentioning
confidence: 99%